Clinical and genetic findings in 13 Chinese children with keratinopathic ichthyosis - Zhou Yang; Zhe Xu; Rui He; Xin Xiang; Bin Zhang; Lin Ma (Wiley, 2023)
ABSTRACT Importance Keratinopathic ichthyosis (KPI) represents a group of predominantly autosomal dominant genodermatoses resulting from mutations in the KRT1, KRT2, or KRT10 genes. In KPI, the relationship between genotype and phenotype is complex. Objective To analyze the clinical manifestations and gene mutations in Chinese patients with KPI. Methods Clinical data were collected from 13 children diagnosed with KPI, and peripheral blood DNA samples were extracted from both the patients and their parents Next‐generation sequencing was performed using a congenital ichthyosis multi‐gene panel, and the selected variants in the patients and their parents were further validated using the Sanger sequencing method. Results Genetic analysis identified missense mutations in either KRT1 or KRT10 in ten patients exhibiting varying degrees of severity and distinct features of epidermolytic ichthyosis. A missense hotspot mutation in KRT2 was identified in one patient with superficial epidermolytic ichthyosis. Additionally, two truncation mutations in KRT10 were detected, leading to the development of generalized ichthyosiform erythroderma. Ear malformation and ectropion at birth, scalp involvement, and palmoplantar hyperkeratosis were observed as early signs of ichthyosis with confetti. Interpretation We analyzed the genotype‐phenotype correlations in KPI, revealing that the types and locations of different mutations are associated with distinct phenotypic characteristics. Oral acitretin could be considered a treatment option for severe patients at an appropriate dosage and timing.